LONELINESS PADA SISWA PELAKU SELF-HARM - Mita Julita, Mita; Meivilona Yendi, Frischa; Syukur, Yarmis; Izzati Adlya, Soeci (Penerbit Lafadz Jaya, 2025)
This study is motivated by the persistence of self-harm behavior among adolescents with feelings of loneliness. Loneliness can arise due to obstacles in establishing social relationships, lack of emotional support, and experiences of rejection from the surrounding environment, causing students who self-harm to feel isolated both at school and at home. This study aims to explore loneliness in self-harming students based on three aspects of loneliness: trait loneliness, social desirability loneliness, and depression loneliness. The study uses a quantitative descriptive method. The population in this study consisted of students from five public high schools in Pariaman City, totaling 4,051 students. The sample was 70 self-harming students selected through purposive sampling. The instrument used was a loneliness questionnaire that has been tested for validity and reliability. Data analysis was performed using descriptive statistics. The results indicate that most self-harming students fall into the moderate category of loneliness across all three aspects. This finding highlights the importance of addressing loneliness as a primary factor in preventing self-harm behavior among adolescents.